Ammonium-substitution for successfully activating the bulk of Keggin acid salts in 1-butanol dehydration. Issue 18 (19th August 2020) - Lang, Charlotte; Schnee, Josefine; Takam Mba, Boris Junior; Devred, François; Gaigneaux, Eric M.
Abstract : Being too bulky and hydrophobic, 1-butanol only reacts at the surface of H3 PW12 O40, but when a part of H + are replaced by NH4 +, butanol can reach remaining inner acid sites inside the bulk and achieves its dehydration with enhanced performance. Abstract : In 1-butanol dehydration (gas phase) on a Keggin heteropolyacid (HPA) catalyst, the large size of 1-butanol and its significant hydrophobicity make the bulk-type (also called pseudo liquid-type) catalytic mechanism impossible. This drastically limits the catalytic effect on the surface of the HPA, with an activity lower than what it could be. To overcome this limitation, partially substituted ammonium Keggin acid salts with the formula (NH4 ) x H3− x PW12 O40 were here synthesized. Still maintaining enough acidity for the dehydration reaction, the replacement of some protons of H3 PW12 O40 with NH4 + increases the hydrophobicity of the crystal matrix and allows 1-butanol to enter the bulk of the salt. This consequently makes the protons inside the solid able to catalyse the reaction. The penetration of 1-butanol in the bulk is demonstrated by a combination of in situ methods (Raman, FTIR and XRD) applied during the pre-treatment of the catalyst and the catalytic reaction. When properly activated the pseudo liquid-type mechanism taking place in (NH4 ) x H3− x PW12 O40 leads to a markedly higher 1-butanol conversion in comparison to the surface-type mechanism which is the only one achieved with the non-modified pristine HPA.